Cultural Differences in the Subjective Experience of Emotion: When and Why They Occur - SCOLLON, Christie N. (Institutional Knowledge at Singapore Management University, 2011)
Cross-cultural comparisons of subjective emotional experience are common, and virtually any comparison of nations or different ethnic groups is bound to yield some differences and some similarities. While nobody doubts the considerable intercultural variability in subjective or self-reports of emotion, more attention needs to be given to when and why and these differences occur. In this article, we explore factors that accentuate or attenuate cultural differences in the subjective experience of emotion. We propose that cultural norms shape emotional experiences to different degrees depending on the time frame of the emotional experience, the valence of the emotion, and even the specific emotion being compared. We review the research that supports this view and we highlight new avenues of research that are likely to shed light on cultural differences in the subjective experience of emotions.